2000
DOI: 10.1038/sj.cgt.7700141
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated p53 gene therapy inhibits human sarcoma tumorigenicity

Abstract: Mutations of the p53 tumor-suppressor gene are the most frequent genetic abnormality in soft tissue sarcomas. Because these rare tumors also respond poorly to standard chemotherapy and bear a 50% 5-year mortality rate, we investigated the possible therapeutic benefits of p53 gene restoration in sarcomas. We constructed Ad5p53, which is an E1A-deleted, replication-deficient adenovirus expressing a cytomegalovirus promoter-driven wild-type p53 cDNA with a Flag sequence tag. SKLMS-1 human leiomyosarcoma cells con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…[27][28][29] Our own investigations utilizing autologous human primary and metastatic sarcoma have demonstrated that clonal expansion of p53-mutated cells in STS confers a distinct metastatic advantage, 30 and we have previously shown that re-expression of wild-type p53 into STS cells harboring a p53 mutation can induce apoptosis, enhance chemosensitivity, inhibit angiogenesis and prolong survival in vitro and in vivo. [15][16][17] Taking these findings into account, it is logical to investigate the role of wild-type p53 as a therapeutic agent in STS, and results from our preclinical sarcoma models are encouraging. For instance, tumor cell transfection with wild-type p53 caused tumor regression in 40% of mice so treated 15 and also restored STS sensitivity to doxorubicin by downregulating the multidrug-resistance protein-1 (MDR1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[27][28][29] Our own investigations utilizing autologous human primary and metastatic sarcoma have demonstrated that clonal expansion of p53-mutated cells in STS confers a distinct metastatic advantage, 30 and we have previously shown that re-expression of wild-type p53 into STS cells harboring a p53 mutation can induce apoptosis, enhance chemosensitivity, inhibit angiogenesis and prolong survival in vitro and in vivo. [15][16][17] Taking these findings into account, it is logical to investigate the role of wild-type p53 as a therapeutic agent in STS, and results from our preclinical sarcoma models are encouraging. For instance, tumor cell transfection with wild-type p53 caused tumor regression in 40% of mice so treated 15 and also restored STS sensitivity to doxorubicin by downregulating the multidrug-resistance protein-1 (MDR1).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Taking these findings into account, it is logical to investigate the role of wild-type p53 as a therapeutic agent in STS, and results from our preclinical sarcoma models are encouraging. For instance, tumor cell transfection with wild-type p53 caused tumor regression in 40% of mice so treated 15 and also restored STS sensitivity to doxorubicin by downregulating the multidrug-resistance protein-1 (MDR1). 16 Furthermore, ITI of FLAGp53 resulted in significant tumor growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations